The Thirty-First Annual Conference of the Association of Muslim Social Scientists - Layla Sein (International Institute of Islamic Thought, 2002)
The Association of Muslim Social Scientists (AMSS) held its thirty first annual conference in Washington, DC, from October 25-27, 2002, with the collaboration of the International Institute of Islamic Thought (IIID. The conference was cosponsored by the School of International Service, American University, and supported by the university's Ibn Khaldun Chair ofislamic Studies, Dr. Akbar Ahmed.